The Humanities and the genesis of higher education regionalization: General Studies and the origin of the regionalization process of the University of Costa Rica - Fonseca Zúñiga, Edgardo (2020)
In 1968, the process of regionalization of the University of Costa Rica (UCR) began, with the creation of regional university centers in remote areas of the Central Valley. This research analyzes the work accomplished by the General Studies in this process. In this way, a review of the educational expansion of Costa Rica in the 1960s and 1970s and its relationship with the state-driven developmental model was carried out. In addition, a contextualization of the higher education model applied in Central America was carried out from the 1960s, where General Education is fundamental. Finally, the role played by the General Studies as a platform to promote the creation of centers that offer university courses beyond the University City Rodrigo Facio is determined. The sources consulted include an extensive bibliographic review and Rectory Reports.